Revealing the causal role of immune cells in malignant neoplasms of the head and neck: insights from Mendelian randomization - Zhou, En; Yuan, MingHao; Zhong, JiaYu; Xiao, XuPing (Frontiers in Oncology, 2024)
BackgroundImmune escape and immunosuppression play crucial roles in the onset and progression of head and neck malignant neoplasms (HNMN). However, previous studies on the relationship between immune cells and HNMN have yielded inconsistent results.MethodsIn this study, we performed bidirectional two-sample Mendelian randomisation (MR) analyses using genome-wide association study (GWAS) and FinnGen databases to examine the association between 731 immune cell features and the risk of HNMN. We conducted sensitivity analyses to assess the robustness of the findings.ResultsSubsequent to false discovery rate (FDR) correction, three immune cell phenotypes were found to have a significant correlation with the risk of HNMN: CD28−CD8+ absolute cells (AC) (inverse-variance weighted [IVW] using the multiplicative random effects model: OR [95%]: 1.325 [1.413 to 1.539], P = 0.0002, Pfdr = 0.054), CD3 on secreting Treg (IVW: OR [95%]: 0.887 [0.835 to 0.941], P = 0.00007, Pfdr = 0.025), and CD3 on resting Treg (IVW: OR [95%]: 0.891 [0.842 to 0.943], P = 0.00006, Pfdr = 0.026). The results of the sensitivity analysis were aligned with the primary findings. No statistically significant effects of HNMN on the immunophenotypes were observed.ConclusionsOur research indicates causal relationships among the three immune cell phenotypes and vulnerability to HNMN, providing new insights into immune infiltration within the HNMN tumour microenvironment and the development of immunotherapy drugs targeting checkpoint inhibitors of HNMN.